Cognitive profiles of poor readers of Kannada - Nag, S; Snowling, M (2011)
The alphasyllabary of Kannada comprises more than 400 symbols called akshara; each symbol is visuo-spatially complex with a consistent representation at the dual levels of the syllable and the phoneme. We investigated reading difficulties in Kannada among 8-12 year old children by conducting a between-groups followed by a case series analysis. We compared the children with reading difficulties with same age competent readers and younger readers who were similar in language level, matched on measures of vocabulary, syntactic processing, and morphological processing. Reading difficulties were characterized by poor akshara knowledge. Concomitant impairments were in syllable and phoneme level phonological skills, in rapid naming and in oral language skills. The case series analysis highlighted the variability of profiles among poor readers with the most common impairments being in akshara knowledge and phonological processing. Sub-groups of poor readers showed additional deficits in oral language, rapid naming, and visual processing skills. Together our findings indicate that the core deficit associated with reading difficulty in the alphasyllabary of Kannada is in the phonological domain. However, accompanying deficits in related skills, including visual processing, can further inhibit reading attainment. The findings from this study support a multifactorial model of reading development. © 2010 Springer Science+Business Media B.V.